2008
DOI: 10.1038/ki.2008.458
|View full text |Cite
|
Sign up to set email alerts
|

Vascular access calcification predicts mortality in hemodialysis patients

Abstract: Vascular calcification is a recognized risk factor for cardiovascular mortality in patients with end-stage renal disease. The aim of this study was to identify risk factors for vascular access calcification and to determine if patients with this disorder are at increased risk of death. Vascular access calcification was found in 49 of 212 hemodialysis patients as measured by plain X-ray (arteriovenous fistula or synthetic graft) in two dimensions. Male gender, diabetes mellitus, and length of time on dialysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 19 publications
2
61
0
2
Order By: Relevance
“…Valvular calcifications were determined by one single observer using echocardiography with an Aspen-ACUSON device (Mountain View, CA) equipped with a 2.5-MHz probe and calcified carotid plaques were defined as echogenic structures showing protrusion into the lumen with focal widening that was 50% greater than the intima media thickness (IMT) of adjacent sites. 27 In addition to single calcification sites, we calculated two semiquantitative calcification scores. 12 First, we determined the Adragao score by analyzing conventional x-rays of the pelvis and hands.…”
Section: Mgp Species Studies Interpretationmentioning
confidence: 99%
See 2 more Smart Citations
“…Valvular calcifications were determined by one single observer using echocardiography with an Aspen-ACUSON device (Mountain View, CA) equipped with a 2.5-MHz probe and calcified carotid plaques were defined as echogenic structures showing protrusion into the lumen with focal widening that was 50% greater than the intima media thickness (IMT) of adjacent sites. 27 In addition to single calcification sites, we calculated two semiquantitative calcification scores. 12 First, we determined the Adragao score by analyzing conventional x-rays of the pelvis and hands.…”
Section: Mgp Species Studies Interpretationmentioning
confidence: 99%
“…It has been shown for the Adragao score that patients with a score of 0 to 2 have a better prognosis than those with a score of 3 to 8. 11,12 Moreover, the presence of calcifications of the heart valves 28 and the AV fistula 27 have been shown to be a mortality risk factor. Bellasi et al 29 reported that simple measures of cardiovascular calcification had a very good correlation with more sophisticated measurements obtained with CT.…”
Section: Mgp Species Studies Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased vascular calcification is a major cause of increased morbidity and mortality in dialysis patients (36,37). Vascular calcification is an active cell-mediated process and likely reflects a transformation of vascular smooth muscle cells to osteoblast-like cells.…”
Section: Inflammation As a Catalyst Of The Vascular Calcification Promentioning
confidence: 99%
“…Similarly, in hemodialysis patients OPG levels were found to be strongly associated with aortic or carotid-to-femoral PWV independently of traditional and uremia-related risk factors including markers of inflammation [25,26,30] . However, other studies in adults and children on hemodialysis treatment were unable to confirm the above findings [19,31] .…”
Section: Opg and Vascular Calcifications In Ckd Patientsmentioning
confidence: 81%